Assessment of 3D Printability of Sweetened Heat Desiccated Concentrated Milk-based Formulations for Preparation of Dairy Sweetmeat (Burfi) - Deepak Vats, Kaushik Khamrui, Writhdhama Prasad, Jatindra K Sahu; Satheeshkanth SSM (Indian Journal of Dairy Science, 2025)
This study was aimed to develop formulations for 3D printing of burfi, with detailed rheological characterization and printability. Milk-concentrate and sugar-based formulations possessed poor printability hence rheology modifiers viz., xanthan gum and corn flour were added. Apparent viscosity, yield stress and storage modulus were critical for 3D printing. Xanthan gum imparted superior print quality as compared corn flour added formulations due to the pronounced shear thinning behaviour. Formulation prepared using milk concentrate to 45% TS, added with 30% sugar and 0.5% xanthan gum exhibited highest dimension accuracy factor (97.01%) and found to be best suited for 3D printing.